USE OF MEMBRANE EMULSION SPAN 80 AND TOPO IN URANIUM EXTRACTION AND STRIPPING - Basuki, Kris Tri; Nurimaniwathy; Puspita, Dian; E.H.B, Bambang (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Membrane emulsion span 80 and TOPO used in uranium extraction and stripping has been done. The extraction was carried outby emulsion membrane H3PO4 in TOPO-Kerosene. The feed or external aqueous phase was uranium in HNO3. The emulgator span-80 was used to obtain a stable emulsion membrane system. The influence factors were percentage of TOPO-Kerosene, time extraction, molarity of external aqueous phase and molarity of internal aqueous. After the emulsion membrane was formed, the extraction and stripping process was performed. The ratio volume feed: volume membrane phase equal to 1 : 1 and volume of 5 % TOPO-Kerosene: Volume 3 M H3PO4 equal 1 : 1 were used. The relatively good yield were obtained at concentration of TOPO in Kerosene and 3 M H3PO4 was 5 %, molarity of internal aqueous phase equal to 1 M, molarity of external aqueous phase 3 M H3PO4 and time extraction equal to 10 minutes with the speed of emulsification was 8000 rpm. At this condition the extraction efficiency of uranium obtained was 97.8 %, the stripping efficiency 52.56 %, and the total efficiency was 53.80 %.